PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Siddi, Purnama; Widiastuti, Libria; Chomsatu, Yuli (Surakarta Management Journal, 2019)
The implementation of CSR in the context of Islam is seen in Islamic Social Reporting or ISR. However, the reporting of Islamic Social Reporting (ISR) in practice and its disclosure is still voluntary. This is due to the absence of standard syariah standard that regulates the reporting of Islamic CSR. The standards for disclosure of sharia CSR issued by the Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) can not be used as a standard of CSR disclosure because it does not mention all CSR related items that a company must disclose. The purpose of this study is to determine the factors that affect the disclosure of Islamic Social Reporting (ISR) on companies listed in the Sharia Indonesia Sharia Index (ISSI) in 2013-2015. Factors used in this study, among others: the size of the company, profitability, and environmental performance. The research population is a company registered in Indonesia Sharia Sharia Index (ISSI) in 2013-2015, with sampling technique using purposive sampling. Analyzer uses multiple linear regression, which previously will be tested classical assumption which include: test of normality, multikolinearitas, heteroskedastisitas, and autokorelasi. The results showed that firm size influenced the disclosure of Islamic Social Reporting (ISR), while profitability and environmental performance had no effect.